Reconhecimento parental e plasticidade fenotípica em duas cultivares de milho em resposta à competição intraespecífica - Cola, Geovana Poton Arcobeli (2017)
Agricultural crops are normally established in monocultures, with proper distribution of water and nutrients, intensive weed managing and a high number of closely related plants, as a way of obtaining higher yields. Such conditions may have increased the capacity of kin recognition in cultivated plants. In view of the above, the aim of this study was to evaluate the kin recognition capacity and the phenotypic plasticity in two maize cultivars (Zea mays L.) in response to the intraspecific competition. For that purpose, two contrasting maize genotypes in terms of levels of domestication (‘Híbrido’ and ‘Crioula’) were cutivated with neighboring plants of different degrees of kinship [treatment between half-sibling, population and strangers (between cultivars)] for an evaluation of their growth and morphological, physiological and biochemical characteristics. The “Hibrido” cultivar presented kin recognition behavior, avoiding competition between related plants, nevertheless presenting competitive behavior when submitted to competition with nonrelated neighbors, altering its pattern of biomass allocation, presenting greater allocation to the roots in comparison to culm and leaf. A lower investment was also observed in morphological structures such as height and, a higher concentration of chlorophyll a and total was observed for “Hibrido” cultivar, when under competition with strangers individuals. The “Crioula” cultivar, on the other hand, presented the same pattern of biomass allocation, morphological structures and physiological between different treatments. For biochemical variables, when under competition with half-sibling individuals and the population, the plants of the cultivar 'Crioula' showed to invest resources for the production of secondary metabolites, suggesting that identity recognition responses on species of unimproved crops may involve metabolic changes in the plant. Therefore, the cultivar 'Crioula' presented low phenotypic plasticity in growth, morphological and physiological attributes in relation to intraspecific competition. Physiological and Growth characteristics were not affected by kin recognition for the ‘Crioula’ cultivar, which showed low phenotypic plasticity in the competition among individuals intraspecific. Due to its higher kin recognition capacity, the “Hibrido” cultivar presented more elevated phenotypic plasticity in attributes related to growth and morphology